Small phenolic compounds as potential endocrine disruptors interacting with estrogen receptor alpha - Alva-Gallegos, Raul; Jirkovský, Eduard; Mladěnka, Přemysl; Carazo, Alejandro (Frontiers in Endocrinology, 2024)
The human body is regularly exposed to simple catechols and small phenols originating from our diet or as a consequence of exposure to various industrial products (e.g., cigarette smoke). Several biological properties have been associated with these compounds such as antioxidant, anti-inflammatory, or antiplatelet activity. Less explored is their potential impact on the endocrine system, in particular through interaction with the alpha isoform of the estrogen receptor (ERα). In this study, human breast cancer cell line MCF-7/S0.5 was employed to investigate the effects on ERα of 22 closely chemically related compounds (15 catechols and 7 phenols and their methoxy derivatives), to which humans are widely exposed. ERα targets genes ESR1 (ERα) and TFF1, both on mRNA and protein level, were chosen to study the effect of the tested compounds on the mentioned receptor. A total of 7 compounds seemed to impact mRNA and protein expression similarly to estradiol (E2). The direct interaction of the most active compounds with the ERα ligand binding domain (LBD) was further tested in cell-free experiments using the recombinant form of the LBD, and 4-chloropyrocatechol was shown to behave like E2 with about 1/3 of the potency of E2. Our results provide evidence that some of these compounds can be considered potential endocrine disruptors interacting with ERα.